PURIFICATION AND CHARACTERIZATION OF AN ANTIMICROBIAL PROTEIN PRODUCED BY BACILLUS AMYLOLIQUEFACIENS MBL27 THAT EXHIBITS ANTIMICROBIAL ACTIVITY AGAINST WOUND PATHOGENS - VIJAYALAKSHMI K,; SUSEELA RAJAKUMAR, (International Journal of Pharma and Bio Sciences, 2016)
The objective of the study was to purify and characterize the antimicrobial protein produced by B.amyloliquefaciens MBL27. An antimicrobial protein isolated from Bacillus amyloliquefaciens MBL27 displays a broad inhibitory spectrum against various Gram negative and Gram positive organisms including clinical pathogens. The proteinaceous compound was isolated from cell-free culture supernatant by (NH4)2SO4 precipitation (40%, w/v saturation) and further purified by ion-exchange chromatography followed by gel filtration on Sephadex G-100 column. The entire purification protocol led to 17.8-fold increase and on SDS-PAGE gels, the protein showed a single band and it is a monomer of 34 kDa. Activity gel electrophoresis also revealed one clear zone of inhibitory activity that corresponded to the band obtained with SDS-PAGE. The inhibitory activity of antimicrobial protein was insensitive to catalase but sensitive to Trichloroacetic acid. It was found to be thermostable and maintained its activity in a wide range of pH.